DINAMIKA SISTEM PENDIDIKAN ISLAM DI DAYAH - Mashuri Mashuri (Jurnal Ilmiah Didaktika, 2013)
Dayah (Islamic boarding school) is the oldest institution in Aceh. It has a positive contribution toward citizen’s capacity building of Aceh, especially in the context of internalizing the Islamic teaching that acts as a social control in Aceh community. Formerly, the form of education in dayah still follow a traditional system, yet, along with the massive development of science and technology, it has adapted with the current situation without ignoring the old system. Many changes occur either in its physic and non-physic form.